Finite element modeling of an energy storing and return prosthetic foot and implications of stiffness on rollover shape. (February 2022) - Cavallaro, Lorenzo; Tessari, Federico; Milandri, Giovanni; De Benedictis, Carlo; Ferraresi, Carlo; Laffranchi, Matteo; De Michieli, Lorenzo
Energy storing and return (ESAR) prosthetic feet showed continuous improvements during the last 30 years. Despite this, standard guidelines are still missing to achieve an optimal foot design in terms of performances. One of the most important design parameters in ESAR feet is the Rollover Shape (RoS). This represents the foot Center of Pressure (CoP) path in a shank-based coordinate system during stance. RoS objectively describes the foot behavior according to its stiffness, which depends on foot geometry and material. This work presents the development of a finite element modeling methodology able to predict the stiffness characteristic of an ESAR foot and its RoS. The validation of the model is performed on a well-known commercially available prosthetic foot both in bench tests and realistic walking scenario. The obtained results confirm an error of +6.1% on stiffness estimation and +10.2% on RoS evaluation, which underlines that the proposed method is a powerful tool able to replicate the mechanical behavior of a prosthetic foot.